The Influence of Leadership with Heart on the Performance of Palm Oil Plantation Company Managers at PT Perkebunan Nusantara III (Persero) - Darmansyah Siregar; Zulkarnain Lubis; Vivi Gusrini Rahmadani; Muhammad Reza Aulia; Mehaga Bastanta Sinulingga (Dinasti Publisher, 2024)
The urgency of this study stems from the multitude of leadership styles that have emerged over the last five years, leaving us uncertain about the most appropriate style to implement in oil palm plantation companies, particularly PT Perkebunan Nusantara III. The problem in this study is that manager performance and leadership vary greatly; some are highly influential and some have no influence. One way to improve manager performance is to apply leadership with heart. Therefore, there needs to be a study on the influence of leadership style with the heart on the performance of oil palm company managers. The anticipated findings aim to determine whether the heart leadership model has a significant impact on manager performance. The targeted output is the mandatory output of a reputable international journal, Scopus Q3, published in the Journal of Leadership Studies, SJR value 0.29, ISSN 1935-262X, and additional outputs of monograph books, international proceedings, and book rights. As for the technology readiness level, this study is included in the category of technology readiness level 1 with a target of technology readiness level 3, namely the formulation of the concept of the heart leadership model on manager performance.